Vocational education and training in Bulgaria : short description - (:unkn) unknown (Publications Office of the European Union, 2018)
This short description helps improve understanding of vocational education and training (VET) in Bulgaria. It covers the main features, highlighting policy developments and current challenges. It is published during the Bulgarian Presidency in the Council of the EU (first half of 2018). "VET in Bulgaria has been mainly school-based. Since 2015, as in many other EU countries, work has focused on reinforcing dual VET to give learners the opportunity to acquire real work experience and understand which skills employers expect and those that can help them succeed. While creating a sustainable national model is still in progress, the country is also working on accompanying policies necessary to make these developments successful." (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Bulgarien